MUSLIM YOUTH, RECEPTION COMMUNITY, AND SOCIAL MEDIA: USTAZ FAHRUDDIN FAIZ PHILOSOPHY - helma winda; Rahma Wati (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The recitation community and social media are alternative routes favored by young Muslims in studying religion. In contrast to recitation, which is carried out directly, this makes young Muslims tend to feel less effective in receiving da'wah material. One of the recitation communities that use social media and attract attention among young Muslims is the Fahruddin Faiz philosophy community at Jendral Sudirman Mosque, Yogyakarta. This study aims to explore how the community of young Muslims engages with Ustaz Fahruddin Faiz's Philosophy lectures through social media. The research data were obtained from interviews with several young Muslims who actively participated in Fahruddin Faiz's philosophical studies, both through social media and directly at the study locations. The research findings show that young Muslims feel more effective and efficient in participating in studies through social media than in person at the Jendral Sudirman Mosque. Several factors are the reasons why young Muslims tend to prefer studies through social media, such as: (1) young Muslims are used to interacting through social media; (2) video studies are packaged as attractively as possible so that young Muslims feel more comfortable in the process of receiving studies; (3) the time to listen to the study is flexible according to the time and opportunities for young Muslims.   Keywords: Muslim youth, social media, Fahruddin Faiz's philosophy study community